Benefits and Barriers to the Adoption of 4D Modeling for Site Health and Safety Management - Swallow, Mark; Zulu, Sam (Frontiers in Built Environment, 2019)
The use of Building Information Modeling processes and supporting technology in the construction industry continues to grow. Its application to various project processes including management of health and safety is acknowledged. The aim of this study was to investigate the current perception of industry professionals regarding the benefits and barriers of the adoption of 4D modeling for management of construction site safety. This is in light of the BIM level 2 framework document PAS1192-6:2018, which promotes the integration of 4D modeling for safer design and construction. The paper reports findings from a questionnaire survey of 141 construction industry professionals. The analysis of data took into account the level of seniority of the participants. The study indicated that 70% of directors/managers and 74% of professionals are aware of 4D. This awareness, however, is not reflected in the current adoption rate as an average of 31.2% of participants had adopted the 4D modeling at their workplace. The study identifies that the perceived primary purpose of 4D is not for health and safety management, although a need for this purpose is evident. The main perceived benefits of 4D were adding value through visualization and clearer communication of project outputs, issues which have positive effects on health and safety management including site planning and logistics. The findings also showed that seniority can influence the perception of barriers to 4D modeling adoption. Such barriers include the cost of training, time to implement and underlining cultural issues. The study recommends an increase in further education and training in BIM and health and safety management. Further evidence-based exploratory studies and promotion of 4D modeling to demonstrate the value of 4D modeling for construction site safety would also be useful as a platform to encourage the uptake of 4D modeling for construction site safety.